A construção de um modelo de gestão descentralizada de resíduos sólidos na Escola Agrotécnica Federal de Uberlândia inspirado nas metas de desenvolvimento do milênio - Melo, Marilda Resende de (2008)
The objective of this work focused on the construction of a decentralized model of solid waste management in Escola Agrotécnica Federal de Uberlândia (EAF-Udi) in order to contribute to the fulfilment of the seventh Millennium Development Goal - Ensure Environmental Sustainability - translated it into local actions. Reports specifically to one of the indicators of this goal, the tenth one, which is to reduce by half until 2015, the proportion of people without sustainable access to drinking water and sanitation, through the adoption of policies and environmental programs. The specific issue to be addressed is contained in part of sanitation concerns and decentralized management of solid waste from School Agrotécnica Federal de Uberlândia, involving the entire school community through environmental health education projects with actions to reduce of waste and to change the destination of it, improving quality of life of every body involved. For the construction of an effective managerial model began with the Differentiated Collection of solid waste generated in the institution, separating them into dry and wet. Later it was made the recovery of dry and wet, giving them the correct destination. The dried were separated by categories (cardboard, PET bootle, cans and plastics) and were sent to reverse logistics. The wet ones, which consisted of organic stuff were reused to their composting in a place of the school. With the effective participation of the community, it was possible to get a significant reduction in the amount of waste brought to the landfill site, guaranteeing a sustainable management. This work contributes for the improvement of life of people. It could be imitated by education institutions similar to the search imitated by other municipalities.